An Analysis Of International Exchange Almuslim Undergraduate’s Experience With Nagoya Gakuin University (Tourism And Citizenship) - Rizkiani, Amelia; Misnar, Misnar (Journal of English Education and Social Science, 2025)
This study examines the experiences of Almuslim University students participating in an international exchange program with Nagoya Gakuin University. The research aims to analyze how educational tourism activities and cross-cultural interactions influence students' development of global citizenship competencies and cultural awareness. This qualitative study employed in-depth interviews with 11 undergraduate students who participated in the exchange program between 2016-2024. Each participant engaged in semi-structured interviews, exploring their experiences, challenges, and personal growth during the program. The interviews were recorded, transcribed, and analyzed using thematic analysis through open coding, axial coding, and selective coding to identify recurring patterns and meaningful themes. Analysis revealed three key themes from the interview data: (1) Enhanced cultural competency, with participants describing significant improvements in their cross-cultural communication abilities and cultural understanding; (2) Deepened environmental awareness, as participants shared their experiences learning about Japanese sustainable tourism practices; and (3) Strengthened global citizenship identity, evidenced by participants' narratives about their changed worldviews and increased international engagement after the program. The interviews highlighted how structured immersion activities particularly contributed to their Japanese language development and cultural adaptation. The findings demonstrate that structured international exchange programs effectively enhance students' global competencies and cultural sensitivity. These outcomes suggest that combining educational tourism with intentional cross-cultural engagement successfully prepares students for global citizenship. Future research should examine the long-term impact of such programs on career development and explore the potential for virtual exchange components.